Nurturing Life Skill Education in an Environment-Based Pesantren - Mahrus As'ad; Lukman Hakim (Jurnal Pendidikan Islam, 2022)
The success of educational institutions can be seen from their ability to develop their students’ life skills including self-potential, skills, and independence development. This study aims to investigate the implementation of environmental-based life skills education at PPBU (Pondok Pesantren Agroecologi Biharul Ulum) Cisarua, Bogor. This study uses a qualitative method. Data was collected by using observation, interview, documentation, and triangulation techniques. Data analysis includes data reduction, data presentation, and drawing conclusions. The results showed that life skills education at PPBU was implemented by using an integrative curriculum based on the theological teachings of the Qur'an with the spirit of local wisdom values. The curriculum was implemented in a number of programs for students’ development in terms of their personal, social, academic, and vocational skills.